PENGEMBANGAN MEDIA SOLAR ESCAPE BERBASIS ESCAPE ROOM EDUKATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM TATA SURYA DI KELAS V SEKOLAH DASAR: Pengembangan Media Solar Escape Berbasis Escape Room Edukatif Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Sistem Tata Surya Di Kelas V Sekolah Dasar - Indah Putri Aprilia; Istianah, Farida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low learning outcomes of students on the Solar System material due to the abstract characteristics of the material and the limited use of interactive learning media. This condition causes students to experience difficulties in understanding concepts such as planet characteristics, rotation, and revolution. This study aimed to develop Solar Escape learning media based on an educational escape room that is valid, practical, and effective in improving science learning outcomes of fifth-grade elementary school students. This research used the Research and Development (R&D) method with the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 22 fifth-grade students at SDN Mulyorejo 2 as the experimental class and 20 fifth-grade students at SDN Dolokgede 1 as the control class. Data collection techniques included observation, interviews, questionnaires, documentation, and pretest-posttest tests. Data were analyzed using validity percentage, practicality, N-Gain scores, and Independent Sample t-Test. The results showed that Solar Escape media obtained a validity score of 93.33% from material experts and 88.75% from media experts, categorized as very valid. The practicality of the media was categorized as very practical based on teacher and student responses. The effectiveness of the media was indicated by the N-Gain score of the experimental class at 0.71 (high category), while the control class obtained 0.37 (moderate category). The Independent Sample t-Test results showed a significance value of <0.05, indicating a significant difference in learning outcomes between the experimental and control classes. Based on these results, Solar Escape media based on an educational escape room is declared valid, practical, and effective for use in science learning on the Solar System material to improve fifth-grade elementary students' learning outcomes.